ORGANIZING AND IMPROVING MATERIALS ACCOUNTING IN ENTERPRISES: ISSUES AND DIRECTIONS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the importance of organizing materials accounting in enterprises and explores ways to improve the efficiency and accuracy of material inventory records. Proper accounting of materials is crucial for ensuring optimal use of resources, controlling costs, and providing reliable financial reporting. The study examines common challenges in material accounting, including errors in inventory tracking, lack of internal controls, and outdated procedures. It also highlights modern approaches for improvement, such as implementation of standardized procedures, automation, and enhanced internal control systems to reduce material misuse and increase productivity. Practical recommendations are provided to help enterprises optimize their material accounting processes and strengthen their financial management.